The Russian Language Is an Instrument of Our Influence - S. V. Lavrov; K. I. Kosarev (Vestnik MGIMO-Universiteta)
Minister for Foreign Relations of Russia S.V. Lavrov’s answers to questions of the Head of Rossotrudnichestvo K.I. Kosachev on «The Russian Voice» Radio Station.